Monitoramento da integridade em estruturas aeronáuticas utilizando materiais piezelétricos e o método dos elementos finitos - Carpena Neto, Mateus (Universidade Federal de São Carlos, 2022)
The maintenance of the aeronautical industry corresponds to a big part of spending from aero companies and the safety during the flight of a commercial airplane it’s extremely important. Therefore, Structural Health Monitoring (SHM) techniques are widely searched to be employed in the aeronautical area as a form of predictive maintenance for predicting aircraft structure failures and defects. Meanwhile, several materials and methods are being studied for application in SHM, such as the use of piezoelectric material in the monitoring of its structural condition. Justified by the need for constant monitoring of structural aircrafts, the present work aims the numerical evaluation of the use of the piezoelectric materials in the monitoring of aircraft structures in SHM techniques. For this, a prototype of a commercial aircraft wing was built in balsa wood and an experimental database was acquired from vibration tests with the piezoelectric sensor monitoring. In addition, the wing was modeled using the Finite Element Method (FEM) to evaluate the model with the built prototype and to perform damage tests imposed on the computational model. The results found showed that for the application of SHM techniques it is necessary to evaluate a working frequency range for this technique. In addition, it was observed that for the monitoring of aeronautical structures changes in natural frequencies and in the Frequency Response Function. The results showed that it is possible to obtain a representative model of an aircraft wing prototype with the piezoelectric material by FEM and that it is valid to use this methodology for the study of SHM techniques. Furthermore, it was possible to observe that the computational model proposed was able to detect structural changes caused by damage to the wing, opening the possibility of implementing SHM techniques.
Structural Health Monitoring in aeronautical structures using piezoelectric materials and the finite element method
Keywords: SHM; Método dos elementos finitos; Finite element method; Modal analysis; Análise modal; Estruturas aeronáuticas; Aeronautical structures; Sensor piezelétrico; Piezoelectric device; ENGENHARIAS::ENGENHARIA MECANICA::MECANICA DOS SOLIDOS